The supplementation of female dogs with live yeast Saccharomyces cerevisiae var. boulardii CNCM I-1079 acts as gut stabilizer at whelping and modulates immunometabolic phenotype of the puppies - Garrigues, Quentin; Mugnier, Amélie; Chastant, Sylvie; Sicard, Flavie; Martin, Jean-Charles; Svilar, Ljubica; Castex, Mathieu; Ramis-Vidal, Manuel Guillermo; Rovere, Nicoletta; Michaud, Laurine; David, Pauline; Mansalier, Elodie; et al. (Frontiers in Nutrition, 2024)
Time around parturition is a stressful period for both bitches and their puppies. The use of probiotics has been proposed, e.g. in pigs, to improve health status of sows, their reproductive performances and in turn, the health and performance of their progeny. The objective of the present study was to evaluate the impact, on both dams and puppies, of a supplementation of bitches with the live yeast Saccharomyces cerevisiae var. boulardii CNCM I-1079 (SB-1079) during the second part of the gestation and the lactation period. A total of 36 bitches of medium and large-sized breeds were enrolled. They were divided into two groups, one of which received 1.3×10 9 colony forming units of live yeast per day. At dam's level, SB-1079 yeast shaped a different microbiota structure between the two groups just after whelping, impacted alpha diversity and some plasma metabolites related to energy metabolism. Regarding reproductive performances, SB-1079 improved gross energy of the colostrum (1.4 vs 1.2 kcal of ME/g) as well as the concentration of protein in milk at Day 7 after parturition (10.4 vs 7.6%). SB-1079 also reduced the odds of having low birth weight in the litter. At puppy's level, a modulation of immunometabolic phenotype is suggested by the observation of increased growth rates during the early pediatric period (i.e. between 21 and 56 days of life, 225 vs 190%) and a decrease of the IL-8:IL-10 ratio after vaccination against rabies (4.2 vs 16.9). Our findings suggest that SB-1079 supplementation during gestation and lactation has the potential to enhance health of bitches and in turn health of puppies through maternal programming.